Ecology of predator-prey and predator-predator interactions in a multi-predator context - Say-Sallaz, Elise (CCSD, 2021)
Large carnivores’ coexistence is common, the aim of that thesis is to understand how it affects predator prey interactions. First part of the thesis is about predator’s Non-Consumptive Effects (NCE hereafter) on prey. Predation risk induce costly behavioural modification for prey, that have an impact on prey population dynamics. For invertebrates these NCE can account for 85% of the total effect of predation. The first chapter is a literature review about NCE for large terrestrial mammals, it highlighted the fact studying NCE requires long term data collection, that reactive (i.e. immediate risk assessment) antipredator response have been less studied that proactive response (long term risk assessment) and that knowledge on NCE mostly come from studies taking only one predator species into account while 90% of the studies took place where several coexist. Hence, second and third chapters focus on reactive response of prey to predators with different hunting mode in order to test the hypothesis that ambush predators (that take prey by surprise) induce higher NCE than cursorial ones (chase down prey), as it has been demonstrated for invertebrates’ species. The second chapter investigate plain zebras (Equus quagga) spatial reactive response to encounters with spotted hyaena (Crocuta crocuta) a cursorial predator and African lion (Panthera leo) an ambush one, with data from GPS collars that were simultaneously deployed on the three species. zebras were twice as likely to leave and they left faster and further away after a lion’s encounter than a hyaena’s one. The third chapter was an experiment to evaluate the immediate behavioural response of the roe deer (Capreolus capreolus) to the Eurasian lynx (Lynx lynx) an ambush predator and the grey wolf (Canis lupus) a cursorial one. Predation risk was simulated at night with playbacks and prey’s response was filmed. Roe deer were more likely to leave the experiment site if lynx vocalises were broadcasted. Results from both chapters support the hypothesis that ambush ...